2015
DOI: 10.18433/j3gc84
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-lowering Activity of Natural and Semi-Synthetic Sterols and Stanols

Abstract: -Consumption of plant sterols/ stanols has long been demonstrated to reduce plasma cholesterol levels. The objective of this review is to demonstrate the lipid-lowering activity and antiatherogenic effects of natural and semi-synthetic plant sterols/ stanols based on evidence from cell-culture studies, animal studies and clinical trials. Additionally, this review highlights certain molecular mechanisms by which plant sterols/ stanols lower plasma cholesterol levels with a special emphasis on factors that affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 180 publications
(250 reference statements)
0
14
0
Order By: Relevance
“…Evidence for novel PSS formulations, such as alternative esters like a disodium ascorbyl phytostanyl phosphate analogue [ 35 ] or a triglyceride-recrystallized PSter complex [ 36 , 37 ] is still too scarce to conclude on a comparable efficacy of established formulations with free and esterified PSter and PStan.…”
Section: Impact Of Plant Sterol and Stanol Sourcementioning
confidence: 99%
“…Evidence for novel PSS formulations, such as alternative esters like a disodium ascorbyl phytostanyl phosphate analogue [ 35 ] or a triglyceride-recrystallized PSter complex [ 36 , 37 ] is still too scarce to conclude on a comparable efficacy of established formulations with free and esterified PSter and PStan.…”
Section: Impact Of Plant Sterol and Stanol Sourcementioning
confidence: 99%
“…This review discusses the current knowledge about plant stanol esters as a dietary treatment option for heterozygous familial hypercholesterolemia (he-FH) children. Since the majority of reviews on dietary phytosterols (the common term for plant sterol and plant stanols) focus on plant sterols [1,2], we solely discuss the role of supplementation of the diet with plant stanols. For a comprehensive coverage of dietary supplementation with both plant sterols and stanols, we refer to the recent European Atherosclerosis Society (EAS) position paper in which the topic is discussed comprehensively at the population level [3].…”
Section: Introductionmentioning
confidence: 99%
“…The phytosterols especially stigmasterol and β-sitosterol may play a pivotal role in maintaining healthy heart cells as these compounds are essential constituents of cellular membranes playing a key role stabilizing the phospholipids, which assist to maintain the fluidity and permeability of cell membrane of heart. Moreover, due to similarity in structure with cholesterol, these phytosterols may acts as cardio protective agents by their lipid lowering effects in the body as elevated level blood cholesterol is consider one major risk factor for the development of the cardiovascular diseases [36,37]. In this regards, McKenney et al [38], also reported that the reductions of cholesterol in body can be achieved by consumption of esterified plant sterols.…”
Section: Resultsmentioning
confidence: 99%